DRIVERS OF COOPERATIVE CHOICE: CANAL MAINTENANCE IN SMALLHOLDER IRRIGATED RICE PRODUCTION IN BENIN - TOTIN, Edmond; LEEUWIS, Cees; van MIERLO, Barbara; MONGBO, ROCH LAMBERT; STROOSNIJDER, Leo; KOSSOU, Dansou (My University, 2014)
Rice production in inland valleys in Southern Benin was initiated by the public sector. The subsequent devolution of responsibility for maintaining the collective irrigation infrastructure to farmers created an opportunity to study the factors that affect cooperation in canal maintenance. We used a social dilemma perspective to compare three rice production areas that differed in the extent of cooperation, based on focus group interviews, surveys, and archival research. The findings draw attention to the nature of the resource, the characteristics of the user group, and farmer-based institutional arrangements as explanatory variables. Specifically these include (1) the balance between water demand and availability, (2) the existence of inequities and privileged positions within the group, and (3) the strength of group organization and the ability to sanction uncooperative behaviour. The existence of alternative sources of livelihood also influenced cooperation. Contrary to our expectations, the largest and most diverse group of producers appeared best organized and equipped to engage in cooperation. Size and diversity might actually allow (1) the emergence of institutional arrangements that can overcome social dilemma situations and demotivation emanating from customary privileges and exemptions and (2) better use of Africa’s irrigation potential.
Keywords: collective action; canal cleaning; water management; inland valleys